Role of the melanocortin system in zebrafish skin physiology. Issue 130 (November 2022) - Leal, E.; Angotzi, A.R.; Gregório, S.F.; Ortiz-Delgado, J.B.; Rotllant, J.; Fuentes, J.; Tafalla, C.; Cerdá-Reverter, J.M.
Abstract: The agouti-signaling protein (ASIP) acts as both a competitive antagonist and inverse agonist of melanocortin receptors which regulate dorsal-ventral pigmentation patterns in fish. However, the potential role of ASIP in the regulation of additional physiological pathways in the skin is unknown. The skin plays a crucial role in the immune function, acting as a physical limitation against infestation and also as a chemical barrier due to its ability to synthesize and secrete mucus and many immune effector proteins. In this study, the putative role of ASIP in regulating the immune system of skin has been explored using a transgenic zebrafish model overexpressing the asip1 gene (ASIPzf). Initially, the structural changes in skin induced by asip1 overexpression were studied, revealing that the ventral skin of ASIPzf was thinner than that of wild type (WT) animals. A moderate hypertrophy of mucous cells was also found in ASIPzf. Histochemical studies showed that transgenic animals appear to compensate for the lower number of cell layers by modifying the mucus composition and increasing lectin affinity and mucin content in order to maintain or improve protection against microorganism adhesion. ASIPzf also exhibit higher protein concentration under crowding conditions suggesting an increased mucus production under stressful conditions. Exposure to bacterial lipopolysaccharide (LPS) showed that ASIPzf exhibit a faster pro-inflammatory response and increased mucin expression yet severe skin injures and a slight increase in mortality was observed. Electrophysiological measurements show that the ASIP1 genotype exhibits reduced epithelial resistance, an indicator of reduced tissue integrity and barrier function. Overall, not only are ASIP1 animals more prone to infiltration and subsequent infections due to reduced skin epithelial integrity, but also display an increased inflammatory response that can lead to increased skin sensitivity to external infections. Highlights: Agouti-signalling protein (ASIP) overexpression induces skin morphological changes. ASIP transgenic fish exhibit higher protein levels in skin mucus after stress events. LPS challenges promote faster proinflammatory response in the skin of ASIP fish. ASIP1 fish exhibit fewer epithelial resistance, indicating reduced tissue integrity.